The Role of Triangular Fibrocartilage Complex in Axial Stability of the Forearm - Zhu, Andy F.; Burns, Geoffrey; Siljander, Breana; Waljee, Jennifer F.; Ozer, Kagan (Journal of Wrist Surgery, 2018)
Background The triangular fibrocartilage complex (TFCC) provides stability to the wrist and disruption of this complex can result in axial instability which can lead to ulnocarpal abutment.Purpose This article determines the individual contributions of the volar radioulnar ligament (VRUL), dorsal radioulnar ligament (DRUL), and foveal attachment of the TFCC to longitudinal stability of the forearm under axial load.Materials and Methods Eighteen cadaveric specimens were randomly assigned into three groups representing the component of the TFCC to be initially transected: VRUL, DRUL, and foveal attachment. Prior to transection, posterioranterior radiographs of the wrist were obtained at 0, 44.5, and 90 N of axial load. Serial transection of the TFCC components were performed with radiographs obtained at each of the aforementioned loads. Ulnar variance was assessed with two-way repeated measures analysis of variance and paired t-tests.Results Transection of the foveal attachment demonstrated a significant change in ulnar variance of 1.5 and 0.6 mm under 45 and 90 N of load, respectively. At 0 N of load, there was no significant change in ulnar variance between an intact wrist and a wrist with all three ligaments transected; however, a significant change in ulnar variance, 1.0 mm, was observed under 90 N of load.Conclusion The foveal attachment of the TFCC provides the largest contribution to axial stability.Clinical Relevance The TFCC provides axial stability to the wrist and disruption of the TFCC may result in change in ulnar variance observed on an axial loaded wrist radiograph.
Keywords: axial instability; triangular fibrocartilage complex; TFCC; ulnocarpal abutment; dynamic X-ray